Alginate as Template in the Preparation of Active Titania Photocatalysts. Issue 2 (10th October 2012) - Buaki‐Sogo, Mireia; Serra, Marco; Primo, Ana; Alvaro, Mercedes; Garcia, Hermenegildo
Abstract A simple and reliable procedure to prepare TiO2 and Au/TiO2 samples with high photocatalytic activity for hydrogen generation from water/methanol mixtures is reported, which uses natural alginate as the templating agent. Aqueous solutions of sodium alginate are flocculated as beads by TiO2+ ions in the presence or absence of AuCl4−. The resulting alginate beads containing approximately 25 wt % of Ti and various Au contents are dehydrated by ethanol washings before drying under supercritical CO2 conditions. The key step in the preparation method is to obtain Au/Ti‐containing alginate aerogels of approximately 700 m2 g−1 Brunauer–Emmett–Teller surface area. The surface area of the TiO2 and Au/TiO2 samples obtained after calcination of the organic biopolymer at 450 °C under air ranges from 187 to 136 m2 g−1, and the Au content has been varied from 1.3 to 0.05 wt % to optimize the photocatalytic activity of the samples. TiO2 forms in the anatase phase according to XRD and Raman spectroscopy. The highest activity Au/TiO2 sample (containing 0.556 wt % of Au) prepared by means of the biopolymer templating method was approximately eight times more active for hydrogen generation using a solar simulator than was an analogous Au‐containing TiO2 P25 sample prepared by means of the conventional deposition–precipitation method.